Deuterium desorption from tungsten using laser heating. (August 2017) - Yu, J.H.; Simmonds, M.; Baldwin, M.J.; Doerner, R.P.
Highlights: Deuterium desorption from tungsten exposed to D plasma at 373 K, and sequential laser heating with pulse widths ranging from 10 ms to 1 s and peak surface temperatures ranging from 500 to 1400 K, are compared to TMAP-7 modeling. TMAP-7 is used to model 3 phases of experiment: D plasma exposure, laser thermal desorption, and temperature programmed desorption (TPD). Model is used to predict D thermal desorption from W for a range of peak surface temperatures and heating durations. Results are compared with previous experiments and modeling of D desorption from Be/D codeposits. Abstract: Retention and desorption of hydrogenic species need to be accurately modeled to predict the tritium inventory of next generation fusion devices, which is needed both for tritium fuel recovery and for tritium safety concerns. In this paper, experiments on thermal desorption of deuterium from intrinsic polycrystalline tungsten defects using laser heating are compared to TMAP-7 modeling. The samples during deuterium plasma exposure were at a temperature of 373 K for this benchmark study with ion fluence of 0.7–1.0 × 10 24  Dm −2 . Following plasma exposure, a fiber laser (λ = 1100 nm) heated the samples to peak surface temperatures ranging from ∼500 to 1400 K with pulse widths from 10 ms to 1 s, and 1 to 10 pulses applied to each sample. The remaining deuterium retention was measured using temperature programmed desorption (TPD). Results show that > 95% of deuterium is desorbed when the peak surface temperature reached ∼950 K for > 1 s. TMAP-7 is used to predict deuterium desorption from tungsten for a range of surface temperatures and heating durations, and is compared to previous work on desorption from beryllium codeposits.